Investigating the impacts of mentoring experiences during teaching practicum on preservice teachers’ sense of preparedness for teaching: a case study on elt students at ud-ufls. - Lê Thị Thùy Nghi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The purpose of this study was to investigate how mentoring experiences during the teaching practicum impact the sense of preparedness of pre-service teachers for the teaching profession. The study used a qualitative research design. Thirty-seven English Language Teaching (ELT) students in their final year at The University of Danang, University of Foreign Language Studies (UD-UFLS) completed a survey questionnaire about their preparation before joining teaching practicum, the support of their mentor teachers during that time and their preparedness to teach after that. Additionally, fifteen pre-service teachers and four mentor teachers from high schools joined an interview. Five random pre-service teachers were also observed during their teaching practicum. Findings indicated that pre-service teachers were well-supported by their mentor teachers, which significantly influenced their sense of preparedness for teaching. In addition, although pre-service teachers were moderately confident with their teaching skills and knowledge, they showed their need to learn and practice more on assessment skills and the support from the university.